2010
DOI: 10.1590/s0100-06832010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Soil shear strength under non-irrigated and irrigated short duration grazing systems

Abstract: Pasture productivity can drop due to soil compaction caused by animal trampling. Physical and mechanical alterations are therefore extremely important indicators for pasture management. The objective of this research was to: draw and evaluate the Mohr failure line of a Red Yellow Latossol under different pasture cycles and natural forest; calculate apparent cohesion; observe possible physical alterations in this soil; and propose a correction factor for stocking rates based on shear strength properties. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Silva et al (2004) and Carvalho et al (2010) verified that soil use and management can influence cohesion intercept, internal friction angle, and, therefore, shear stress. Larney & Kladivko (1989) reported that shear stress increased in the surface of soils cultivated with moldboard plow.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Silva et al (2004) and Carvalho et al (2010) verified that soil use and management can influence cohesion intercept, internal friction angle, and, therefore, shear stress. Larney & Kladivko (1989) reported that shear stress increased in the surface of soils cultivated with moldboard plow.…”
Section: Resultsmentioning
confidence: 89%
“…The authors reported that higher levels of organic matter, associated with the soil aggregation model, the level of root entanglement in the soil, and with the presence of physical and chemical bonds between particles in native environments, resulted in higher soil aggregation and, therefore, in higher mechanical resistance. However, Carvalho et al (2010) found that irrigated pasture and natural bush have similar shear strength, higher than that of nonirrigated pasture. Moreover, the authors stated that the shear strength of soil samples with lower water content (-33 kPa) does not differ between managements.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The soil of this study was not compacted, as the values found ranged from 0.48 to 0.52 m 3 m -3 in the layer 0-3 cm and from 0.46 to 0.51 m 3 m -3 in the layer 10-13 cm, indicating absence of soil compaction (Table 6). Carvalho et al (2010), working with a Red Latosol pasture cultivated with Brachiaria brizantha cv MG-5 Vitória under animal trampling, obtained a TPV value of 0.48 m 3 m -3 , indicating absence of compaction.…”
Section: Resultsmentioning
confidence: 99%
“…Soil compaction, characterized by the reduction of the porous space under external soil pressure, can be a major problem in heavily mechanized and/or trampled areas and is one of the key factors associated with soil degradation (Kondo & Dias Junior, 1999;Mosaddeghi et al, 2007;Carvalho et al, 2010;Pires et al, 2012). Soil compaction can result in a reduction in the productivity and longevity of pastures (Imhoff et al, 2000) and accelerate erosion processes (Oliveira et al, 2004).…”
Section: Introductionmentioning
confidence: 99%